Dramaturgi Pekerja Anak Dalam Pengelolaan Ekonomi Sebagai Bentuk Pemenuhan Interpretasi Keluarga - Anjelina Putri Aisyah; Reefadhinta Novta Amelia (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Children are part of the family who have rights and obligations through the process of growth and development. The purpose of this study is to uncover and understand the dramaturgical process involved in the role of child labourers as they are involved in managing the family economy. This research will examine how child labourers choose certain characters or roles in carrying out the profession. The research was conducted in Alun- Alun as a public facility that is often used as a location for child labourers to carry out their activities every night. This research uses a qualitative approach by using data collection instruments directly in the field. This research was analysed from the observation, interview, documentation and data presentation process. The theory used is Social Dramatugi theory to find out the character shown by child workers in their profession and Interpretation Fulfilment theory to find out the experience of child workers in helping families. The results of this study show that the behaviour patterns of child workers from the frontstage show the attitude of child workers in the internal and external character of children. The backstage part of child labourers is also able to show the life of child labourers in the family. So that the pattern of responsibility owned is the basis for their encouragement to continue working every day even though there are children's time that must be sacrificed.